Earlier egg laying commencement of the Collared Flycatcher (Ficedula albicollis) during twenty years - Michal Baláž; Roman Slobodník; Vladimír Slobodník; Mária Balážová (Tichodroma, 2022)
Increasing temperature causes changes in breeding phenology in many bird species. One of the most prominent changes related to higher temperature is the earlier laying of eggs. We focused on breeding of the Collared Flycatcher (Ficedula albicollis) to find the differences in start of egg laying during the period of 20 years (2001–2020) in a permanently monitored breeding site in central Slovakia. Analysing 762 broods of the Collared Flycatcher we found that there are significant differences in start of egg laying between the breeding seasons and that the first egg day is significantly affected by the spring temperature. Our results show that the Flycatchers lay eggs significantly earlier. The first egg day at the end of the 2020 decade is shifted by 5–6 days compared to the years around the year 2000. The shift of the median laying day at the same period was by 1–2 days.